Startegi Memperkuat Ketahanan Komunitas Berbasis Kearifan Suku Bajau dalam Menghadapi Ancaman Bencana Ekologis - Emi Setyaningsih (Jurnal Ketahanan Nasional, 2023)
This study aims to analyze the local wisdom of the Bajau Tribe, as well as their strategies to strengthen wisdom-based community resilience in facing the threat of ecological disasters. Ecological disasters are a global problem that can threaten the entire population of the earth, including the Bajau Tribe community who live in the waters of Torosiaje village, Gorontalo. The people of Nusantara actually have wisdom that is empirically proven to be able to minimize environmental damage caused by human activities. Unfortunately, this wisdom began to be abandoned because it was considered unscientific and outdated.This research is literature research with hermeneutic methods. This method is used to find and find the essential meaning contained in the object of research, namely local wisdom possessed by the Bajau Tribe regarding their views on natural and human relations, then how the knowledge system based on the worldview is able to strengthen the resilience of the Bajau community in facing the threat of ecological disaster. The results of this study show that the local wisdom possessed by the Bajau Tribe which is manifested in the knowledge system and attitudes of the Bajau Tribe in managing the natural environment in the sea can strengthen community resilience in facing the threat of ecological disaster. The strategy carried out to strengthen the resilience of their community is to synergize the knowledge system of the Bajau Tribe with science and present a legal instrument with an environmental paradigm derived from the wisdom of the tribe.Â